Phytotoxicity and phytoremediation potential of Lemna minor exposed to perfluorooctanoic acid - Azam Noori; Lorena Corbelli; Erin Lincoln; Sara Thomas; Jasmine Jones; Sara L. Nason; Jason C. White; Riley Lewis; Christy L. Haynes (Frontiers in Plant Science)
Perfluorooctanoic acid (PFOA) is one of the highly toxic compounds which was phased out of application in consumer products in 2015 due to its harmful effects on human and environmental health. However, this chemical was in use for many years and is still found in water resources. This study focuses on the physiological response of duckweed (Lemna minor) exposed to PFOA so as to determine phytotoxicity and the potential of this aquatic species to remove PFOA from the environment. A time-dependent phytotoxicity assay showed that exposure to 0.1 µg/L PFOA for 14 days resulted in the loss of chlorophyll pigment and 15-25% more chlorosis than in controls. Although exposure to PFOA for seven days resulted in chlorosis, no significant impact on physiological parameters such as photosynthetic pigment or anthocyanin content were detected. The analysis of cellular size on day zero and seven of the experiment showed that the control group showed significantly larger cell size after seven days (213 ± 6.5 µm²) compared with the day zero group (186 ± 18 µm²), while the size of the PFOA exposed group (198 ± 13 µm²) did not change significantly after seven days compared with the day zero group. The nuclear size increased significantly by 13% upon exposure to PFOA compared with the controls (ρ < 0.0001). The concentration of essential elements K, Cu, Fe, Mn, Zn, Mo were reduced in L. minor exposed to PFOA compared with the controls by 39.6, 33.4, 42.1, 35.2, 31.9, 40.2%, respectively. Additionally, PFOA accumulated in L. minor fronds and roots with an average bioaccumulation factor of 56 ± 7. Overall, while some symptoms of toxicity were observed, this study shows that L. minor can tolerate up to 0.1 µg/L PFOA, a commonly found concentrations in water bodies, and can remove PFOA from water. This study provides invaluable information regarding the phototoxicity impacts of PFOA on aquatic species and the potential for aquatic phytoremediation of PFOA.